Production potential and economics of aonla based Agri-horti system under rainfed semi-arid ecosystem of western India (Indian Journal of Arid Horticulture, 2013)
A field trial was carried out to find out the practicalities and economics of suitable and profitable cucurbitaceous  vegetables as intercrops (bottle guard,pumpkin,bitter guard, cucumber, sponge guard) on 7 to 10 years aonla orchard during  the year of 2007-2011 at the Experimental Farm of Central Horticultural Experiment Station (CIAH), Vejalpur, Panchmahals  (Godhra), Gujarat under rainfed semi arid ecosystem of western India. Among the different cucurbitaceous vegetable tried as  intercrops, aonla + bottle gourd combination fetched the maximum net economic return of Rs. 147312.80/ ha with the B: C  ratio 4.44 followed by aonla + pumpkin (Rs. 100525.00/ha with the B: C ratio 3.11) whereas the lowest economic return was  recorded in control followed by aonla + sponge gourd purely under rainfed conditions of semi-arid ecosystem of western  India. Based on the results, it has been confirmed that the aonla + bottle gourd combination is most effective to generate  substantial additional income without affecting the aonla yield when compared to other treatment combinations. In order to  its remunerativeness as additional income, it needs to be popularized among the farmers which not only will enhance the  system productivity but also the space left the aonla orchards will be utilized efficiently.
Keywords: Aonla; intercrops; cucurbits; productivity; economic return